Health Promotion Activities Among Older Women: Insights from Pender’s Health Promotion Model - Selman Hussain Faris; Ghazwan Abdulhussein Al-Abedi; Haqi Ismael Mansoor (National Journal of Community Medicine)
Aims: The study examines factors associated with older women's participation in health promotion activities.